Gingival Depigmentation Using Diode 980 nm and Erbium-YAG 2940 nm Lasers: A Split-Mouth Clinical Comparative Study - Zaid Kamel Jnaid Harb; Walid El-Sayed; Jumma Alkhabuli (International Journal of Dentistry)
Aim of the Study. This study aimed to compare the effectiveness of diode laser (980 nm) and erbium-YAG laser (2940 nm) for gum depigmentation. Background. Gingival hyperpigmentation, “black gum,” refers to black discrete single or multiple pigments on the gingiva. Several factors may play a role in gingival hyperpigmentation ranging from physiologic pigmentation to manifestations of systemic diseases. Several techniques have been used for gingival depigmentation to lighten its color. Methods. Fifteen patients exhibiting nonsmoking melanin hyperpigmentation, with the mean age of 28.6 ± 7.8 years, were recruited. The facial gingiva of the anterior teeth and premolars of each jaw was divided into two halves. The right or left side of each jaw quadrant randomly received either diode laser operating at 980 nm wavelength or erbium-YAG laser at 2940 nm. Parameters such as degree of gingival depigmentation, bleeding, pain, patient satisfaction, and wound healing were assessed and compared between the two techniques. The subjects were followed up to six months for melanin pigmentation recurrence. Results. Both techniques were efficient for gingival depigmentation. Nevertheless, bleeding during surgery was statistically higher for Er:YAG laser technique as compared to diode laser. Wound healing showed statistically nonsignificant differences between the two lasers, although Er:YAG seems to give better outcomes than the diode. The patients were satisfied with both laser techniques during and after gingival depigmentation. However, the pain score was higher for Er:YAG laser than for diode laser. Conclusion. This study demonstrated that both lasers’ techniques are efficient for gingival depigmentation. However, diode laser seems to show less painful experience and relatively better bleeding control.